Reduced radial displacement of the gastrocnemius medialis muscle after electrically elicited fatigue - Macgregor, L. J.; Ditroilo, M.; Smith, I. J.; Fairweather, M. M.; Hunter, A. M. (Journal of Sport Rehabilitation, 2016)
Context: Assessments of skeletal-muscle functional capacity often necessitate maximal contractile effort, which exacerbates muscle fatigue or injury. Tensiomyography (TMG) has been investigated as a means to assess muscle contractile function after fatigue; however, observations have not been contextualized by concurrent physiological measures.